2017
DOI: 10.1590/1807-3107bor-2017.vol31.0109
|View full text |Cite|
|
Sign up to set email alerts
|

Microtensile bond strength of CAD/CAM materials to dentin under different adhesive strategies

Abstract: The present study aimed to evaluate the microtensile bond strength (µTBS) of novel computer-aided design/computer-aided manufacturing (CAD/CAM) restorative materials to dentin using different adhesive strategies. Thirty-two crowns were milled using CAD/CAM materials (Vita Mark II as control, Vita Suprinity, Vita Enamic and Lava Ultimate) and luted to dentin using different resin cements (RelyX ARC, RelyX Unicem 2 and RelyX Ultimate). The specimens were stored in 100% relative humidity at 37°C for 24 h and sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
(39 reference statements)
3
27
0
1
Order By: Relevance
“…Predomination of cohesive failure in IPS e.max CAD and Vita Enamic prove that bonding of cement to the surface of tooth structure and restoration exceeds the inherent strength of the cement itself, also the surface treatment of the tooth structure improved bonding with the cement so, no adhesive failure occurred. This was found in agreement with an invitro study (39) , which reported that Vita Enamic surface treatment dissolve the glassy matrix and create a honeycomb-like surface rough and micromechanically retentive. This can explain the high percentage of cohesive failure of cement for Vita Enamic luted with RelyX Ultimate resin cement (50,51) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Predomination of cohesive failure in IPS e.max CAD and Vita Enamic prove that bonding of cement to the surface of tooth structure and restoration exceeds the inherent strength of the cement itself, also the surface treatment of the tooth structure improved bonding with the cement so, no adhesive failure occurred. This was found in agreement with an invitro study (39) , which reported that Vita Enamic surface treatment dissolve the glassy matrix and create a honeycomb-like surface rough and micromechanically retentive. This can explain the high percentage of cohesive failure of cement for Vita Enamic luted with RelyX Ultimate resin cement (50,51) .…”
Section: Discussionsupporting
confidence: 92%
“…7,No. 2 This was in agreement with in-vitro studies (39,40) , which concluded that the bond strength results could be affected by the difference in the elasticity moduli,Vita Enamic obtained higher micro tensile bond strength values, the modulus of elasticity of Vita Enamic is (30 GPa) (31) , which is comparable to that of dentin (16 -20.3 GPa)and lower than IPS e-max (95 GPa) (32) , and Vita Suprinity (70 GPa) (33) . Furthermore, the copolymerization process which occur between the 14% resin and methacrylate monomers with acidic group present in Rely X Ultimate cement resulting in the higher microtensile bond strength values of Vita Enamic (41,42) .…”
Section: Discussionsupporting
confidence: 88%
“…The modulus of elasticity of ENA higher than LVU Moreover, LVU have similar modulus of elasticity to dentin and resin cements. This agreement with Bellan et al (13) whose found that the more modulus of elasticity of material (ENA) tend to start the fracture at the adhesive interface at lower values than the more resilient materials (LVU), which could explain the lower µTBS values of ENA.…”
Section: Discussionsupporting
confidence: 90%
“… 1 2 3 4 5 6 As attempts to achieve a durable bond, manifold micromechanical (mechanical, chemical, and laser irradiation) and chemical (silicon coatings, use of coupling agents) surface conditioning strategies are in use. 1 2 3 4 7 8 9 10 …”
Section: Introductionmentioning
confidence: 99%